1988
DOI: 10.1128/jb.170.5.2148-2152.1988
|View full text |Cite
|
Sign up to set email alerts
|

Levels and activities of nitrogenase proteins in Azotobacter vinelandii grown at different dissolved oxygen concentrations

Abstract: Azotobacter vinelandii was grown diazotrophically at different dissolved oxygen concentrations (in the range of 3 to 216 FM) in sucrose-linited continuous culture. The specific nitrogenase activity, measured on the basis of acetylene reduction in situ, was dependent solely on the growth rate and was largely independent of oxygen and sucrose concentration. FeMo (Avl) and Fe (Av2) nitrogenase proteins were quantified after Western blotting (immunoblotting). When the cultures were grown at a constant dilution rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…2A). This observation is consistent with previous analyses and supports the observation that nitrogenase activity is optimal under conditions of high Fe protein to MoFe protein ratios (13,14). Interestingly, the abundances of transcripts of nonessential nif genes (28) downstream of nifK increased by only 2-to 14-fold ( Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…2A). This observation is consistent with previous analyses and supports the observation that nitrogenase activity is optimal under conditions of high Fe protein to MoFe protein ratios (13,14). Interestingly, the abundances of transcripts of nonessential nif genes (28) downstream of nifK increased by only 2-to 14-fold ( Fig.…”
Section: Resultssupporting
confidence: 81%
“…Under N-fixing conditions, nitrogenase components make up nearly 10% of the total cellular proteins, the majority of which are structural proteins (14). The catalytic components necessary for FeMo-co biosynthesis are presumably necessary in much smaller amounts.…”
Section: Resultsmentioning
confidence: 99%
“…This possibility can be excluded by previous findings showing that neither the cellular level nor the turnover of the nitrogenase polypeptides of A. vinelandii is affected by oxygen (7). Moreover, since it was shown that the cellular level of both nitrogenase polypeptides is largely independent of D, it was concluded that the D-dependent increase of the cellular nitrogenase activity is regulated by the supply of reducing equivalents and energy (7). The present investigation confirms the latter mechanism.…”
Section: Discussionsupporting
confidence: 75%
“…For example, it was shown with A. vinelandii growing at high dissolved oxygen concentrations that the respiratory activity does not significantly increase with an increase in the dissolved oxygen concentration (25). Moreover, cultures of A. vinelandii exhibited comparable cellular contents and nitrogenase activities in spite of considerable differences in cellular oxygen consumption (7,13). Finally, it has been demonstrated that oxygen enters the cells of A. vinelandii without impairing the function of nitrogenase (21).…”
mentioning
confidence: 98%
See 1 more Smart Citation